Detection of Endometrial TB in Patients with AUB using PCR Method of Assessment of Menstrual Blood Flow of Iraqi Females - Maad Mehdi Shallal,1 Farah AbdulHussein Salih Al-Asadi2 , Mohammad Ibrahim Mizaal3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Iraq still considered one of the countries in the region with high prevalence of TB, there areabout 20000 patients, accounts for 3% of the total number of cases, and the estimated death from TB exceeds4000 per year. TB in Iraq until nowadays considered a health, public and social problem, and because ofthe wars and political problems, many programs, campaigns, and researches were hundred by this situationObjective: To detect endometrial Tuberculosis in women complaining from AUB (abnormal uterinebleeding) using real time PCR method of assessment via taking an endocervical swab.Patients and methods: Prospective cross-sectional study carried at Department of obstetrics and gynecologyin Baghdad teaching hospital /medical city over a period of eight months starting from Octuber2019, toAugest2020. A total of 60 women complaining from abnormal uterine bleeding(AUB) who were scheduledto have endometrial biopsy for histopathology by dilatation and curettage(D&C), endocervical swab assessedfor female genital tuberculosis(FGTB) by real time PCR.Results: Out of 60 samples taken 6 were positive by real time PCR 10%, while there was only one casepositive by histopathology 1.66% which was also positive by PCR the same patient gave history of pulmonaryTB and received a nine month course of treatment, according to these findings the sensitivity of PCR foundto be 100% while the specificity92% and an accuracy of 92%.Conclusion: Real time PCR considered one of the valuable diagnostic tools for mycobacterium tuberculosis,and because Iraq still showing high incidence of the disease, one should suspect mycobacterium tuberculosisin any women complaining from abnormal uterine bleeding and offer PCR in addition to other diagnosticmodalities, luckily it will allow treatment at an early stage of the disease.